An integrative taxonomic approach reveals exceptional species diversity of Burmoniscus from China (Crustacea: Isopoda: Oniscidea) - Yao, Chonghui; Zhu, Qidi; Zong, Zili; Jiang, Chao; Li, Weichun (Journal of systematics and evolution : JSE, 2025)
Burmoniscus Collinge, 1916, the most species‐rich genus within the family Philosciidae, presents significant taxonomic challenges due to interspecific morphological convergences and intraspecific variations. This study employs an integrative taxonomic framework combining morphological examination with molecular phylogenetic analyses and species delimitations based on the sequence data of a mitochondrial COI gene and three nuclear genes (18S rRNA, 28S rRNA, and NaK) to classify Burmoniscus species. Our results reveal 21 species Burmoniscus from China, including 12 new species (Burmoniscus acutatus Li & Jiang, sp. nov., B. obscurus Li & Jiang, sp. nov., B. cuneatus Li & Jiang, sp. nov., B. rectangulatus Li & Jiang, sp. nov., B. solus Li & Jiang, sp. nov., B. spinellosus Li & Jiang, sp. nov., B. cordatus Li & Jiang, sp. nov., B. trispinatus Li & Jiang, sp. nov., B. rotundus Li & Jiang, sp. nov., B. simplicissimus Li & Jiang, sp. nov., B. rubustus Li & Jiang, sp. nov., and B. variatus Li & Jiang, sp. nov.) and firstly report two species, B. schultzi Taiti, Ferrara & Kwon, 1992 and B. comtus (Budde‐Lund, 1894) from China. This work highlights the critical role of integrative taxonomy in clarifying species boundaries and uncovering hidden diversity in terrestrial isopods. This study employs an integrative taxonomic framework combining morphological examination with molecular phylogenetic analyses and molecular species delimitations to classify Burmoniscus species. Our results reveal 21 species Burmoniscus, including 12 new species and firstly report two species, B. schultzi Taiti, Ferrara & Kwon, 1992 and B. comtus (Budde‐Lund, 1894) from China. This work highlights the critical role of integrative taxonomy in clarifying species boundaries and uncovering hidden diversity in terrestrial isopods.